Impact of food, housing, and transportation insecurity on ART adherence: a hierarchical resources approach. Issue 4 (3rd April 2017) - Cornelius, Talea; Jones, Maranda; Merly, Cynthia; Welles, Brandi; Kalichman, Moira O.; Kalichman, Seth C.
ABSTRACT: Antiretroviral therapy (ART) has transformed HIV into a manageable illness. However, high levels of adherence must be maintained. Lack of access to basic resources (food, transportation, and housing) has been consistently associated with suboptimal ART adherence. Moving beyond such direct effects, this study takes a hierarchical resources approach in which the effects of access to basic resources on ART adherence are mediated through interpersonal resources (social support and care services) and personal resources (self-efficacy). Participants were 915 HIV-positive men and women living in Atlanta, GA, recruited from community centers and infectious disease clinics. Participants answered baseline questionnaires, and provided prospective data on ART adherence. Across a series of nested models, a consistent pattern emerged whereby lack of access to basic resources had indirect, negative effects on adherence, mediated through both lack of access to social support and services, and through lower treatment self-efficacy. There was also a significant direct effect of lack of access to transportation on adherence. Lack of access to basic resources negatively impacts ART adherence. Effects for housing instability and food insecurity were fully mediated through social support, access to services, and self-efficacy, highlighting these as important targets for intervention. Targeting service supports could be especially beneficial due to the potential to both promote adherence and to link clients with other services to supplement food, housing, and transportation. Inability to access transportation had a direct negative effect on adherence, suggesting that free or reduced cost transportation could positively impact ART adherence among disadvantaged populations.